The Role of Applying Some Artificial Intelligence Technologies in Improving the Quality of External Auditing (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
The world is witnessing a technological transformation under the Fourth Industrial Revolution، with artificial intelligence (AI) emerging as a tool capable of changing professional work methods. This development has affected external auditing through its ability to analyze big data and enhance the accuracy of error detection. This study aims to demonstrate the role of applying expert systems and machine learning in improving the quality of external auditing in Syria. The study adopted a descriptive-analytical approach، describing some AI techniques and analyzing their impact on audit quality. As a practical application، a field study was conducted by distributing a questionnaire to a sample of auditors in Syria. (50) Questionnaires were distributed، (46) were returned، and (42) were valid for analysis using SPSS. The results demonstrated the role of the studied AI techniques in the quality of external auditing. The research recommends that audit firms adopt machine-learning techniques to improve audit quality، develop training programs in the use of expert systems، and conduct studies to measure the impact of other AI technologies such as natural language processing and artificial neural networks.
Keywords: Artificial intelligence، external audit، audit quality.